Novel Syntheses of Some 1, 2, 4-Triazoles as Potent Bacteriocidal Agents - Ram Janam Singh; Dharmendra Kumar Singh (E-Journal of Chemistry)
A facile syntheses of 4-aryl-5-(isomeric pyridoyl)-3H-1, 2, 4-triazoles as potent bacteriocidal agents are described. The newly synthesized compounds were characterized by spectral and elemental analyses. Some compounds were screened for their antibacterial activity against S. aureus, E. coli, B. subtilis and P.aeruginosa. All compounds carrying 1, 2, 4- triazole moiety showed significant biological activity